A novel vision-based PET bottle recycling facility. (20th December 2016) - He, Xiangyu; He, Zaixing; Zhang, Shuyou; Zhao, Xinyue
Abstract: Post-consumer PET bottle recycling is attracting increasing attention due to its value as an energy conservation and environmental protection measure. Sorting by color is a common method in bottle recycling; however, manual operations are unstable and time consuming. In this paper, we design a vision-based facility to perform high-speed bottle sorting. The proposed facility consists mainly of electric and mechanical hardware and image processing software. To solve the recognition problem of isolated and overlapped bottles, we propose a new shape descriptor and utilize the support vector data description classifier. We use color names to represent the colors in the real world in order to avoid problems introduced by colors that are similar. The facility is evaluated by the target error, outlier error and total error. The experimental results demonstrate that the facility we developed is capable of recycling various PET bottles.